2017
DOI: 10.1063/1.5001322
|View full text |Cite
|
Sign up to set email alerts
|

Realization of zero-field skyrmions with high-density via electromagnetic manipulation in Pt/Co/Ta multilayers

Abstract: Taking advantage of the electron-current ability to generate, stabilize, and manipulate skyrmions prompts the application of skyrmion multilayers in room-temperature spintronic devices. In this study, the robust high-density skyrmions are electromagnetically generated from Pt/Co/Ta multilayers using Lorentz transmission electron microscopy. The skyrmion density is tunable and can be significantly enhanced. Remarkably, these generated skyrmions after optimized manipulation sustain at zero field with both the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 31 publications
1
63
0
1
Order By: Relevance
“…Advances, particularly in interfacial Dzyaloshinskii-Moriya (DM) interactions, 10 have largely overcome the challenges associated with room-temperature stability. 4,11 Few approaches have been demonstrated that can stabilize skyrmions at zero applied magnetic field, but include rapid quenching, 8,12 pulsed electrical currents, 13 geometric confinement, 14,15 or pinning the skyrmions with nanostructures 16,17 . These approaches place restrictions on the skyrmion system, limiting both fundamental research and eventual device architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Advances, particularly in interfacial Dzyaloshinskii-Moriya (DM) interactions, 10 have largely overcome the challenges associated with room-temperature stability. 4,11 Few approaches have been demonstrated that can stabilize skyrmions at zero applied magnetic field, but include rapid quenching, 8,12 pulsed electrical currents, 13 geometric confinement, 14,15 or pinning the skyrmions with nanostructures 16,17 . These approaches place restrictions on the skyrmion system, limiting both fundamental research and eventual device architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the host material and generation mechanisms have been extended from the initial chiral magnets with Dzyaloshinskii-Moriya interaction (DMI) [4][5][6] to centrosymmetric magnets with uniaxial magnetic aniso tropy [7,8] and to magnetic multilayers with interfacial DMI. [17,18] Unless external manipulation or the proliferation of defects promote their existence at zero field, [19][20][21][22] vortex-like spin textures can only be obtained as an excitation state under the stimuli of certain magnetic fields. The corresponding magnetic ground state exhibits a periodic helical spin order with uniform stripe domains.…”
mentioning
confidence: 99%
“…Magnetic bubbles have been found in a high-Q system, i.e., when Q > 1, 17 and in some materials with Q $ 1, such as in hexaferrites, 16 MnNiGa, 22 and Pt/Co/Ta multilayers. 23,24 Doped transition-metal oxides like manganite systems are well known for their rich physical properties and magnetic phase transitions due to the combination of coupling between charge, spin, orbital, and broad degrees of freedom. 9,[25][26][27] Biskyrmions have been found in La 2-2x Sr 1 þ 2x Mn 2 O 7 (x ¼ 0.315) 9 and spontaneous bubbles by doping different amounts of Ru are reported in La 1.2 Sr 1.8 (Mn 1-y Ru y ) 2 O 7 .…”
mentioning
confidence: 99%
“…The spin reorientation transition is considered to play a critical role in the generation of the topological spin configuration. 23,24 The corresponding helical magnetic spin configuration and sine-like M y profile are schematically described in Fig. 1(i).…”
mentioning
confidence: 99%